The epigenome: the next substrate for engineering. Issue 1 (December 2016) - Park, Minhee; Keung, Albert; Khalil, Ahmad
Abstract We are entering an era of epigenome engineering. The precision manipulation of chromatin and epigenetic modifications provides new ways to interrogate their influence on genome and cell function and to harness these changes for applications. We review the design and state of epigenome editing tools, highlighting the unique regulatory properties afforded by these systems.